The Greening of Development : No Growth Without Energy - Carraro, Carlo; Massetti, Emanuele (2012)
Economic development increases the demand for energy. This is true for countries at all income levels, although as economic growth progresses, the demand tends to increase more in the low- and middle-income countries than in high-income ones. But energy remains a key ingredient for economic growth at all stages of development.